A wear-resistant composite additive for hydraulic oil and preparation method thereof
By using a composite additive of modified wear-resistant agent and modified antioxidant to form nanosilica lanthanum and polyp-divinylbenzene composite particles, as well as an antioxidant protective layer of sulfonamide and cysteine, the existing hydraulic pressure problem is solved. It is difficult for oil additives to improve wear resistance, anti-corrosion and anti-rust properties at the same time, achieving efficient lubrication and long life of hydraulic oil under harsh working conditions.
Patent Information
- Application Number
- CN202411025789.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-30
AI Technical Summary
Existing hydraulic oil additives are difficult to improve the wear, corrosion and rust resistance of hydraulic oil at the same time, especially in harsh working conditions.
A composite additive of modified wear-resistant agent and modified antioxidant is used. The modified wear-resistant agent forms nanosilica lanthanum particles and poly(p-divinylbenzene) composite particles, and the modified antioxidant forms sulfonamide and cysteine. reaction to form a hydrophobic and antioxidant protective layer.
Significantly improves the wear resistance, anti-corrosion and anti-rust properties of hydraulic oil, extends the service life of the hydraulic system, and maintains good lubrication effect under harsh working conditions.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oil additives, in particular to a hydraulic oil wear-resistant composite additive and a preparation method thereof. Background Art
[0002] Hydraulic technology is one of the key technologies to realize modern transmission and control. Compared with other transmissions, hydraulic transmission has the characteristics of compact structure, sensitive response, and easy to realize automatic operation. Hydraulic oil is an important part of hydraulic technology. In the hydraulic system, it plays the role of energy transmission, system lubrication, corrosion prevention, and rust prevention. With the continuous improvement of the requirements for lubrication conditions, a single lubricant is difficult to meet the lubrication needs, and research has begun to turn to composite additives. Adding additives with certain functions to hydraulic oil is an effective method to significantly improve the friction and wear state of hydraulic oil.
[0003] Antioxidants and antiwear agents are important additives to improve the performance of lubricating oils. Antioxidants use their own reduction reactions to prevent hydrocarbon groups from being oxidized, thus providing continuous and stable lubrication. Antiwear agents react with metal surfaces to form a chemical reaction film, which avoids direct contact between friction pairs, reduces wear, and can significantly improve lubrication under harsh working conditions. Therefore, developing hydraulic oil additives with excellent performance and improving the friction reduction and anti-wear properties of hydraulic oils are important research directions. Summary of the invention
[0004] The purpose of the present invention is to provide a hydraulic oil wear-resistant composite additive and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a hydraulic oil wear-resistant composite additive, wherein the hydraulic oil wear-resistant composite additive comprises a modified wear-resistant agent and a modified antioxidant.
[0006] Furthermore, the modified wear-resistant agent is prepared from lanthanum oxide, sodium silicate and p-divinylbenzene.
[0007] Furthermore, the modified antioxidant is prepared from aminosulfonic acid, 5-chlorovaleryl chloride and cysteine.
[0008] Furthermore, a method for preparing a hydraulic oil wear-resistant composite additive comprises the following preparation steps:
[0009] (1) 46 to 72 parts of sodium silicate are placed in a smelting crucible, and 50 to 84 parts of lanthanum oxide are melted to obtain a molten liquid, the crucible is placed in a furnace, and when the ambient temperature reaches 600° C., the molten liquid is atomized and sprayed to obtain nano-silicon lanthanum particles;
[0010] (2) placing 13 to 37 parts of nano-silicon lanthanum, 0.5 to 2.5 parts of silane coupling agent, and 38 to 68 parts of ethanol in a high temperature machine, stirring at 1400 rpm / min for 30 to 50 minutes, to obtain modified nano-silicon lanthanum;
[0011] (3) adding 0.4-1.2 parts of p-divinylbenzene to 68-90 parts of dilute hydrochloric acid solution at -5-5°C, stirring at 500 rpm for 30-40 min, then adding 0.1-0.3 parts of modified nano-silicon lanthanum and stirring for 2 h, ultrasonicating for 1 h, and then dropping 30-46 parts of ammonium persulfate dilute hydrochloric acid solution at -5-5°C and 300 rpm, stirring for 4 h, standing for 16 h, centrifuging, and rinsing twice with deionized water and ethanol to obtain a modified wear-resistant agent;
[0012] (4) Dissolve 11 to 19 parts of aminosulfonic acid and 1 to 3 parts of 4-dimethylaminopyridine in 42 to 58 parts of chloroform, add 14 to 22 parts of 5-chlorovaleryl chloride at -5-5°C and 600 rpm with stirring, heat to 15 to 25°C and react for 2 to 4 hours, stand and separate, extract the organic layer three times with 42 to 66 parts of ethyl acetate and 27 to 39 parts of water, concentrate, and dry at 80°C for 6 hours to obtain sulfonic acid amide;
[0013] (5) 13 to 21 parts of cysteine, 29 to 37 parts of acetonitrile, and 7 to 9 parts of acetic acid are mixed, and 7 to 11 parts of sulfonic acid amide are added at 80° C. and 500 rpm for reaction for 5 to 9 hours, and 20 to 50 parts of methanol, 90 to 120 parts of water, and 2 to 5 parts of Na2CO3 solid are added, and the mixture is stirred at 0 to 10° C. and 700 rpm for 1 hour, and the solid is filtered and dried at 80° C. for 6 hours to obtain a modified antioxidant;
[0014] (6) 5 to 8 parts of modified anti-wear agent, 0.6 to 1.4 parts of modified antioxidant, 0.01 to 0.05 parts of defoaming agent, and 0.03 to 0.05 parts of anti-emulsifier are mixed uniformly to obtain a hydraulic oil anti-wear composite additive.
[0015] Furthermore, the atomization spraying conditions in step (1) are: atomization medium Ar gas, atomization pressure 3.0-4.0 MPa, atomization flow rate 18-30 m 3 / min.
[0016] Furthermore, the silane coupling agent in step (2) is one or more of A151 and A171.
[0017] Furthermore, the dilute hydrochloric acid solution in step (3) is 1 mol / L, the content of ammonium persulfate in the dilute hydrochloric acid solution is 9.36 g / L, the centrifugal speed is 3000 rpm / min, and the centrifugal time is 5 to 15 min.
[0018] Furthermore, the conditions for concentrating the organic phase in step (4) are: vacuum degree -0.1MPa to -0.07MPa, and concentration time 1h.
[0019] Furthermore, the defoaming agent in step (6) is one or more of polydimethylsiloxane, polypropylene glycol, and polyoxypropylene oxide glycerol ether.
[0020] Furthermore, the anti-emulsifier in step (6) is one or more of T1001, T1002, and SP169.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] The invention utilizes a modified anti-wear agent and a modified antioxidant to mix to prepare a composite additive, so as to achieve the effects of wear resistance, corrosion resistance and rust prevention.
[0023] Firstly, the modified wear-resistant agent uses a tightly coupled vacuum induction furnace to combine lanthanum oxide with sodium silicate in the form of a spray to form nano-silicon lanthanum particles with a smooth surface. The nano-silicon lanthanum particles enter the friction surface to form a lubricating film, reduce the roughness of the metal surface, and enhance the wear resistance. The silane coupling agent then combines with the hydroxyl groups on the surface of the powder to improve the stability. On this basis, the agent interacts with p-divinylbenzene and in-situ polymerization is used to form composite particles of poly-p-divinylbenzene-coated silicon lanthanum, which improves the adsorption force between the metal and the surface, forms a protective layer, reduces wear, and extends the service life.
[0024] Secondly, the modified antioxidant is prepared from aminosulfonic acid, 5-chlorovaleryl chloride and cysteine; the present invention utilizes 5-chlorovaleryl chloride to react with the amino group in aminosulfonic acid to form sulfonic acid amide, introduces hydrophobic groups, reduces liquid penetration, and preliminarily achieves an anti-corrosion effect; at the same time, the sulfonic acid group can hydrogen-bond chelate with the metal surface to form a stable chemical bond, reduce oxygen entry, and enhance the anti-rust performance; then the chlorine group in the sulfonic acid amide is hydrogen-bonded with the ester carbonyl of cysteine to form an ether bond, achieve a hydrophobic effect, and further enhance the anti-corrosion performance; on this basis, a thiol group is introduced, the sulfur-hydrogen bond is broken during oxidation, and hydrogen atoms are provided to interrupt the oxidation chain reaction, thereby preventing oxidation damage. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the hydraulic oil wear-resistant composite additive prepared in the following examples are as follows:
[0027] Corrosion test: Mix the composite additives of the embodiment and the comparative example with the hydraulic oil and test them according to GB / T5096.
[0028] Four-ball machine test: The composite additives of the embodiment and the comparative example were mixed evenly with the hydraulic oil and tested according to GB / T3142.
[0029] Liquid phase corrosion: The composite additives of the embodiment and the comparative example were mixed evenly with the hydraulic oil, and the test was performed according to GB / T11143.
[0030] Example 1
[0031] (1) 46 parts of sodium silicate were placed in a melting crucible, and 50 parts of lanthanum oxide were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 600°C, an atomizing medium of Ar gas was used, the atomizing pressure was 3.0 MPa, and the atomizing flow rate was 18 m 3 / min atomizing and spraying the melt to obtain nano-silicon lanthanum particles;
[0032] (2) placing 13 parts of nano-silicon lanthanum, 0.5 parts of A151, and 38 parts of ethanol in a high temperature machine and stirring at 1400 rpm / min for 30 min to obtain modified nano-silicon lanthanum;
[0033] (3) 0.4 parts of p-divinylbenzene were added to 68 parts of dilute hydrochloric acid solution at -5°C, stirred at 500 rpm for 30 min, then 0.1 parts of modified nano-silicon lanthanum were added and stirred for 2 h, ultrasonicated for 1 h, and then 30 parts of ammonium persulfate dilute hydrochloric acid solution with a content of 9.36 g / L was added dropwise at -5°C and 300 rpm, stirred for 4 h, allowed to stand for 16 h, centrifuged at 3000 rpm / min for 5 min, rinsed twice with deionized water and ethanol, and a modified wear-resistant agent was obtained; the dilute hydrochloric acid solution was 1 mol / L;
[0034] (4) 11 parts of aminosulfonic acid and 1 part of 4-dimethylaminopyridine were dissolved in 42 parts of chloroform, 14 parts of 5-chloropentanoyl chloride were added at -5°C and 600 rpm with stirring, the temperature was raised to 15°C for reaction for 2 hours, and the layers were allowed to stand for stratification. The organic layer was extracted three times with 42 parts of ethyl acetate and 27 parts of water, concentrated at a vacuum degree of -0.1 MPa for 1 hour, and dried at 80°C for 6 hours to obtain sulfonic acid amide;
[0035] (5) 13 parts of cysteine, 29 parts of acetonitrile and 7 parts of acetic acid were mixed, and 7 parts of sulfonic acid amide were added at 80°C and 500 rpm for 5 h, and 20 parts of methanol, 90 parts of water and 2 parts of Na2CO3 solid were added, and stirred at 0°C and 700 rpm for 1 h. The solid was filtered and dried at 80°C for 6 h to obtain a modified antioxidant;
[0036] (6) 5 parts of modified anti-wear agent, 0.6 parts of modified antioxidant, 0.01 parts of polypropylene glycol and 0.03 parts of T1001 were mixed evenly to obtain a hydraulic oil anti-wear composite additive.
[0037] Example 2
[0038] (1) 59 parts of sodium silicate were placed in a melting crucible, and 67 parts of lanthanum oxide were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 600°C, an atomizing medium of Ar gas was used, the atomizing pressure was 3.5 MPa, and the atomizing flow rate was 24 m 3 / min atomizing and spraying the melt to obtain nano-silicon lanthanum particles;
[0039] (2) placing 25 parts of nano-silicon lanthanum, 1.5 parts of A171, and 53 parts of ethanol in a high temperature machine and stirring at 1400 rpm / min for 40 min to obtain modified nano-silicon lanthanum;
[0040] (3) 0.8 parts of p-divinylbenzene was added to 79 parts of dilute hydrochloric acid solution at 0°C, stirred at 500 rpm for 35 min, then 0.2 parts of modified nano-silicon lanthanum was added and stirred for 2 h, ultrasonicated for 1 h, and then 38 parts of 30 parts of dilute hydrochloric acid solution of ammonium persulfate with a content of 9.36 g / L was added dropwise at 0°C and 300 rpm, stirred for 4 h, allowed to stand for 16 h, centrifuged at 3000 rpm / min for 10 min, rinsed twice with deionized water and ethanol, and a modified wear-resistant agent was obtained; the dilute hydrochloric acid solution was 1 mol / L;
[0041] (4) 15 parts of aminosulfonic acid and 2 parts of 4-dimethylaminopyridine were dissolved in 50 parts of chloroform, and 18 parts of 5-chloropentanoyl chloride were added at 0°C and 600 rpm with stirring, and the temperature was raised to 20°C for reaction for 3 hours. The organic layer was allowed to stand for stratification, and the organic layer was extracted three times with 54 parts of ethyl acetate and 33 parts of water, and the mixture was concentrated at a vacuum degree of -0.085 MPa for 1 hour and dried at 80°C for 6 hours to obtain sulfonic acid amide;
[0042] (5) 17 parts of cysteine, 33 parts of acetonitrile, and 8 parts of acetic acid were mixed, and 9 parts of sulfonic acid amide were added at 80° C. and 500 rpm for 7 h. 35 parts of methanol, 105 parts of water, and 3.5 parts of Na2CO3 solid were added, and stirred at 5° C. and 700 rpm for 1 h. The solid was filtered and dried at 80° C. for 6 h to obtain a modified antioxidant;
[0043] (6) 6.5 parts of modified anti-wear agent, 1.0 part of modified antioxidant, 0.03 parts of polydimethylsiloxane and 0.04 parts of T1002 were mixed evenly to obtain a hydraulic oil anti-wear composite additive.
[0044] Example 3
[0045] (1) 72 parts of sodium silicate were placed in a melting crucible, and 84 parts of lanthanum oxide were melted to obtain a melt. The crucible was placed in a furnace. When the ambient temperature reached 600°C, an atomizing medium of Ar gas was used, the atomizing pressure was 4.0 MPa, and the atomizing flow rate was 30 m 3 / min atomizing and spraying the melt to obtain nano-silicon lanthanum particles;
[0046] (2) placing 37 parts of nano-silicon lanthanum, 2.5 parts of A151, and 68 parts of ethanol in a high temperature machine and stirring at 1400 rpm / min for 50 min to obtain modified nano-silicon lanthanum;
[0047] (3) 1.2 parts of p-divinylbenzene were added to 90 parts of dilute hydrochloric acid solution at 5°C, stirred at 500 rpm for 40 min, then 0.3 parts of modified nano-silicon lanthanum were added and stirred for 2 h, ultrasonicated for 1 h, and then 46 parts of ammonium persulfate dilute hydrochloric acid solution with a content of 9.36 g / L was added dropwise at 5°C and 300 rpm, stirred for 4 h, allowed to stand for 16 h, centrifuged at 3000 rpm / min for 15 min, rinsed twice with deionized water and ethanol, and a modified wear-resistant agent was obtained; the dilute hydrochloric acid solution was 1 mol / L;
[0048] (4) 19 parts of aminosulfonic acid and 3 parts of 4-dimethylaminopyridine were dissolved in 58 parts of chloroform, and 22 parts of 5-chlorovaleryl chloride were added at 0°C and 600 rpm with stirring, and the temperature was raised to 25°C for reaction for 3 hours. The organic layer was allowed to stand for stratification, and the organic layer was extracted three times with 66 parts of ethyl acetate and 39 parts of water, concentrated at a vacuum degree of -0.07 MPa for 1 hour, and dried at 80°C for 6 hours to obtain sulfonic acid amide;
[0049] (5) 21 parts of cysteine, 37 parts of acetonitrile and 9 parts of acetic acid were mixed, 11 parts of sulfonic acid amide were added at 80°C and 500 rpm for 9 hours, 50 parts of methanol, 120 parts of water and 5 parts of Na2CO3 solid were added, and the mixture was stirred at 10°C and 700 rpm for 1 hour. The solid was filtered and dried at 80°C for 6 hours to obtain a modified antioxidant;
[0050] (6) 8 parts of modified anti-wear agent, 1.4 parts of modified antioxidant, 0.05 parts of polyoxypropylene oxyethylene glycerol ether, and 0.05 parts of SP169 were mixed evenly to obtain a hydraulic oil anti-wear composite additive.
[0051] Comparative Example 1
[0052] The difference between Comparative Example 1 and Example 2 is that there are no steps (1) and (2), and step (3) is changed to: 0.8 parts of p-divinylbenzene is added to 79 parts of dilute hydrochloric acid solution at 0°C, stirred at 500 rpm for 35 minutes, and then 38 parts of dilute hydrochloric acid solution of ammonium persulfate with a content of 9.36 g / L is added dropwise at 0°C and 300 rpm, stirred for 4 hours, to obtain a modified anti-wear agent; the dilute hydrochloric acid solution is 1 mol / L. The remaining steps are the same as in Example 2.
[0053] Comparative Example 2
[0054] The difference between Comparative Example 2 and Example 2 is that step (3) is omitted, and step (6) is changed to: 6.5 parts of modified nano-silicon lanthanum, 1.0 parts of modified antioxidant, 0.03 parts of polydimethylsiloxane, and 0.04 parts of T1002 are mixed evenly to obtain a hydraulic oil wear-resistant composite additive. The remaining steps are the same as those of Example 2.
[0055] Comparative Example 3
[0056] The difference between Comparative Example 3 and Example 2 is step (1), which is changed to: 59 parts of sodium silicate, 67 parts of lanthanum oxide, and 168 parts of water are mixed, stirred at 600 rpm for 1 hour, transferred into a reaction kettle, reacted at 220° C. and 450 rpm for 24 hours, cooled naturally to room temperature, washed with deionized water until the solution pH value is 7, and then dried in an oven at 80° C. for 16 hours to obtain nano-silicon lanthanum particles. The remaining steps are the same as those in Example 2.
[0057] Comparative Example 4
[0058] The difference between Comparative Example 4 and Example 2 is that there is no step (2). The remaining steps are the same as those in Example 2.
[0059] Comparative Example 5
[0060] The difference between Comparative Example 5 and Example 2 is that step (4) is omitted, and step (5) is changed to: 17 parts of cysteine and 5 parts of 4-dimethylaminopyridine are dispersed in 33 parts of tetrahydrofuran, 18 parts of 5-chlorovaleryl chloride are added at 25° C. and 600 rpm with stirring, and after reacting for 2 hours, the mixture is centrifuged at 1800 rpm / min for 10 minutes to obtain a modified antioxidant. The remaining steps are the same as those in Example 2.
[0061] Comparative Example 6
[0062] The difference between Comparative Example 6 and Example 2 is that there is no step (5), and step (6) is changed to: 6.5 parts of modified anti-wear agent, 1.0 parts of sulfonic acid amide, 0.03 parts of polydimethylsiloxane, and 0.04 parts of T1002 are mixed evenly to obtain a hydraulic oil anti-wear composite additive. The remaining steps are the same as in Example 2.
[0063] Comparative Example 7
[0064] The difference between Comparative Example 7 and Example 2 is that step (4) is omitted, and step (5) is changed to: 17 parts of cysteine, 33 parts of water, 15 parts of aminosulfonic acid, and 5 parts of 4-dimethylaminopyridine are mixed, stirred at 25° C. and 500 rpm for 7 hours, 54 parts of ethyl acetate are added for extraction 3 times, concentrated at a vacuum degree of 0.085 MPa for 1 hour, and dried at 50° C. for 6 hours to obtain a modified antioxidant. The remaining steps are the same as those in Example 2.
[0065] Effect example
[0066] Table 1 below shows the performance analysis results of the hydraulic oil wear-resistant composite additives of Examples 1 to 3 and Comparative Examples 1 to 7 of the present invention.
[0067] Table 1
[0068] Corrosion test / grade Four-ball machine test Pb / N Liquid phase corrosion Example 1 1b 918 Rust-free Example 2 1b 926 Rust-free Example 3 1b 921 Rust-free Comparative Example 1 2b 669 Slight rust Comparative Example 2 2b 725 Slight rust Comparative Example 3 2c 632 Slight rust Comparative Example 4 2b 684 Slight rust Comparative Example 5 3b 717 Severe rust Comparative Example 6 3b 693 Severe rust Comparative Example 7 3b 672 Severe rust
[0069] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that nano-silicon lanthanum can enter the friction surface, form a lubricating film, and enhance wear resistance; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the use of divinylbenzene to coat nano-silicon lanthanum powder can improve the adsorption force between the metal and form a protective layer to reduce wear; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that the nano-silicon lanthanum prepared by tightly coupled vacuum induction has a smooth surface, which can reduce the roughness of the metal surface and achieve a wear-resistant effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that the powder modified by the silane coupling agent It has better stability, avoids reaction with external free radicals, and reduces wear; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the sulfonic acid group of aminosulfonic acid is chelated with the metal surface to form a stable chemical bond, reduce the entry of oxygen, and achieve an anti-rust effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the sulfhydryl group in cysteine breaks during oxidation, providing hydrogen atoms to interrupt the oxidation reaction and avoid oxidation corrosion; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 7, it can be found that 5-chlorovaleryl chloride reacts with the amino group of aminosulfonic acid to form an amide bond, introduces a hydrophobic group, prevents liquid from entering, and effectively improves the anti-corrosion effect.
[0070] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered as exemplary and non-restrictive in all respects.
Claims
1. A method for preparing a wear-resistant composite additive for hydraulic oil, characterized in that: The method comprises the following preparation steps: (1) 46-72 parts of sodium silicate are placed in a smelting crucible, and 50-84 parts of lanthanum oxide are melted to obtain a molten liquid. The crucible is placed in a furnace. When the ambient temperature reaches 600°C, the molten liquid is atomized and sprayed to obtain nano-silicon lanthanum particles. (2) placing 13-37 parts of nano-silicon lanthanum, 0.5-2.5 parts of silane coupling agent, and 38-68 parts of ethanol in a high temperature machine, stirring at 1400 rpm / min for 30-50 min, to obtain modified nano-silicon lanthanum; (3) Add 0.4-1.2 parts of p-divinylbenzene to 68-90 parts of dilute hydrochloric acid solution at -5-5°C, stir at 500rpm for 30-40min, then add 0.1-0.3 parts of modified nano-silicon lanthanum and stir for 2h, ultrasonicate for 1h, then dropwise add 30-46 parts of ammonium persulfate dilute hydrochloric acid solution at -5-5°C and 300rpm, stir for 4h, let stand for 16h, centrifuge, rinse twice with deionized water and ethanol to obtain a modified wear-resistant agent; (4) Dissolve 11-19 parts of aminosulfonic acid and 1-3 parts of 4-dimethylaminopyridine in 42-58 parts of chloroform, add 14-22 parts of 5-chloropentanoyl chloride at -5-5°C and 600 rpm with stirring, raise the temperature to 15-25°C and react for 2-4 hours, let stand to separate, extract the organic layer three times with 42-66 parts of ethyl acetate and 27-39 parts of water, concentrate, and dry at 80°C for 6 hours to obtain sulfonic acid amide; (5) 13-21 parts of cysteine, 29-37 parts of acetonitrile and 7-9 parts of acetic acid were mixed, and 7-11 parts of sulfonic acid amide were added at 80°C and 500 rpm for 5-9 hours, and 20-50 parts of methanol, 90-120 parts of water and 2-5 parts of Na2CO3 solid were added, and the mixture was stirred at 0-10°C and 700 rpm for 1 hour. The solid was filtered and dried at 80°C for 6 hours to obtain a modified antioxidant; (6) Evenly mix 5-8 parts of modified anti-wear agent, 0.6-1.4 parts of modified antioxidant, 0.01-0.05 parts of defoaming agent and 0.03-0.05 parts of anti-emulsifier to obtain a hydraulic oil anti-wear composite additive.
2. The method for preparing a wear-resistant composite additive for hydraulic oil according to claim 1, characterized in that: The atomization spraying conditions in step (1) are: atomization medium Ar gas, atomization pressure 3.0-4.0 MPa, and atomization flow rate 18-30 m³ / min.
3. The method for preparing a wear-resistant composite additive for hydraulic oil according to claim 1, characterized in that: The silane coupling agent in step (2) is one or more of A151 and A171.
4. The method for preparing a wear-resistant composite additive for hydraulic oil according to claim 1, characterized in that: The dilute hydrochloric acid solution in step (3) is 1 mol / L, the content of ammonium persulfate in the dilute hydrochloric acid solution is 9.36 g / L, the centrifugal speed is 3000 rpm / min, and the centrifugal time is 5 to 15 min.
5. The method for preparing a wear-resistant composite additive for hydraulic oil according to claim 1, characterized in that: The conditions for concentrating the organic phase in step (4) are: vacuum degree -0.1MPa~-0.07MPa, and concentration time 1h.
6. The method for preparing a wear-resistant composite additive for hydraulic oil according to claim 1, characterized in that: The defoaming agent in step (6) is one or more of polydimethylsiloxane, polypropylene glycol, and polyoxypropylene oxyethylene glycerol ether.
7. The method for preparing a wear-resistant composite additive for hydraulic oil according to claim 1, characterized in that: The anti-emulsifier in step (6) is one or more of T1001, T1002, and SP169.
Citation Information
Patent Citations
Carbocatalysts for polymerization
CN103347904A
Rubber composition and self-lubricating rubber sealing strip prepared from same
CN105694463A